ANALISIS KANDUNGAN INFORMASI DAN EFEK INTRA INDUSTRI PENGUMUMAN STOCK SPLIT YANG DILAKUKAN OLEH PERUSAHAAN BERTUMBUH DAN TIDAK BERTUMBUH - Almilia, Luciana Spica; Kristijadi, Emanuel (Journal of Indonesian Economy and Business, 2005)
The objective of this research is to examine empirically about the information contentand intra industry effect of stock split announcement. The analysis include three aspects:information content, risk (beta) and intra industry effect of stock split announcement bygrowth firm and not growth firm.The sample of this research is 79 reporter firm (consist of 59 growth firm and 20 notgrowth firm) and 166 non reporter firms during the period of 1997 â 2002. The result ofthis research show that stock split has information content which is negatively respondendand statistically significant responded by the market around the date of stock splitannouncement. The difference between beta growth firms and not growth firms after stocksplit announcement is significant. The intra industry effect of stock split announcement iscompetitive effect.Keywords: stock split, intra industry effect, competitive effect, information content